Answer:
[tex]f(1) = 2[/tex]
[tex]f(n) = f(n-1) + 2[/tex] where [tex]n\geq 2[/tex]
Step-by-step explanation:
Given
2,4,6,8...
Required
Which function determines the sequence
Represent the terms with n where n is 1,2,3....
Analyzing each term:
[tex]f(1) = 2[/tex]
[tex]f(2)= 4 = 2 + 2 = f(1) +2[/tex]
[tex]f(3)= 6 = 4 + 2 = f(2) +2[/tex]
[tex]f(4)= 8 = 6 + 2 = f(3) +2[/tex]
Notice that each term is an addition of the previous term and 2
In other words:
[tex]f(n) = f(n-1) + 2[/tex]
However, the function is only effective for values of n greater than or equal to 2
So: [tex]n\geq 2[/tex]